Evolutionary history of the reef fish Anisotremus interruptus (Perciformes: Haemulidae) throughout the Tropical Eastern Pacific - Palmerín Serrano, Paola Nallely (2020)
The Tropical Eastern Pacific (TEP) is a dynamic coastal environment characterized by a complex system of oceanic processes and discontinuous rocky habitats. These features, in conjunction with the ecological and physiological characteristics of Anisotremus interruptus , might limit gene flow and shape the evolutionary history of the species. In this study, we investigate the evolutionary history of the reef fish A. interruptus (and its Atlantic sister species A. surinamensis) throughout its range in the TEP, using two mitochondrial (cox1 and cytb) and two nuclear markers (S7 and RAG1). We found three genetic groups of A. interruptus with recent divergence times from the Galapagos Archipelago, Revillagigedo Archipelago, the continental TEP, and A. surinamensis the sister specie from the Atlantic. The haplotype mtDNA networks show A. surinamensis in a central position with respect to Pacific genetic haplogroups, whereas nDNA networks show mixed haplotypes between the four genetic groups. In the species tree, A. surinamensis appears as the sister species of all the Pacific samples and the Galapagos Archipelago population emerges as a genetically distinctive group. The samples from the Revillagigedo Archipelago also constitute a genetic distinctive group, closely related to the continental samples. Continental individuals do not show significant genetic structure and exhibit a population expansion during the Pleistocene. The sandy gaps of the TEP not appear to act as barriers isolating populations of A. interruptus, whereas the open sea gap between the oceanic islands and the continental coast do.